Disruption of protein geranylgeranylation in the cerebellum causes cerebellar hypoplasia and ataxia via blocking granule cell progenitor proliferation - Qi Cheng; Jing Wu; Yingqian Xia; Qing Cheng; Yinjuan Zhao; Peixiang Zhu; Wangling Zhang; Shihu Zhang; Lei Zhang; Yushan Yuan; Chaojun Li; Guiquan Chen; et al. (Molecular Brain, 2023)
Abstract The prenylation of proteins is involved in a variety of biological functions. However, it remains unknown whether it plays an important role in the morphogenesis of the cerebellum. To address this question, we generated a mouse model, in which the geranylgeranyl pyrophosphate synthase (Ggps1) gene is inactivated in neural progenitor cells in the developing cerebellum. We report that conditional knockout (cKO) of Ggps1 leads to severe ataxia and deficient locomotion. To identify the underlying mechanisms, we completed a series of cellular and molecular experiments. First, our morphological analysis revealed significantly decreased population of granule cell progenitors (GCPs) and impaired proliferation of GCPs in the developing cerebellum of Ggps1 cKO mice. Second, our molecular analysis showed increased expression of p21, an important cell cycle regulator in Ggps1 cKO mice. Together, this study highlights a critical role of Ggpps-dependent protein prenylation in the proliferation of cerebellar GCPs during cerebellar development.